2003
DOI: 10.1002/jssc.200301585
|View full text |Cite
|
Sign up to set email alerts
|

Increased size‐sorting performance in gravitational SPLITT by using a pinched sample inlet design

Abstract: Increased size-sorting performance in gravitational SPLITT by using a pinched sample inlet design Split-flow thin fractionation is a continuous, flow-assisted separation technique for sorting macromolecules and particulate matter on a preparative scale. On reducing the thickness of the sample inlet conduit of a gravitational split-flow thin fractionation channel, size-sorting performance is found to increase since particles that are continuously fed into the channel can be more rapidly compressed toward the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…A PI-GSF channel was built in house as described in previous reports [13,14]. Four different channel dimensions were used in this study to achieve particle separation at each different cut-off diameter.…”
Section: Pi-gsfmentioning
confidence: 99%
See 2 more Smart Citations
“…A PI-GSF channel was built in house as described in previous reports [13,14]. Four different channel dimensions were used in this study to achieve particle separation at each different cut-off diameter.…”
Section: Pi-gsfmentioning
confidence: 99%
“…The theoretical relationship between cut-off diameter and flow rate conditions can be found in the literature [9,13,14]. In every fractionation step (corresponding to each different cut-off diameter), a two stage fractionation procedure was used: a rough cut at a relatively high feed rate followed by a precision cut at a low feed rate by re-injecting the collected particle suspension.…”
Section: Pi-gsfmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it is demonstrated that GSF can be effectively utilized for the continuous separation of sea sediments and that the resulting fractions of a narrow diameter range can be analyzed for the study of the size-dependent levels of PCDD/Fs and heavy metals. To enhance SPLITT fractionation efficiency, our work adopts the pinched inlet SPLITT channel design (shown in Figure ) that was developed in a previous work by reducing the thickness of the sample inlet conduit of GSF channel. By applying the pinched inlet design to the GSF channel, particles leaving the inlet splitter can be quickly transported and efficiently pushed against the upper wall of the GSF channel by the carrier stream so that the number of particles leaving from an ideal trajectory expected during sample injection is decreased to some degree.…”
mentioning
confidence: 99%
“…1,8,9 Conventionally, GSF is carried out in a thin ribbon-like channel equipped with two splitters between the top and bottom inlets and outlets of the channel, respectively. 10 A schematic view of a GSF channel is shown in Figure 1(a).…”
Section: Introductionmentioning
confidence: 99%